Comparison of reamed long and short intramedullary nail constructs in unstable intertrochanteric femur fractures: A biomechanical study - Blum, Laura E. (OTA Int, 2020)
OBJECTIVES: There is no definitive evidence to guide clinicians in their decision-making for implant choice regarding long or short intramedullary nails for unstable fracture patterns. Historically short nails were associated with higher rates of perisprothetic fractures which seem to have improved with newer designs. Long intramedullary nails have higher blood loss and time under anesthesia. The purpose of this study was to assess stability of long and short intramedullary nail constructs in unstable intertrochanteric fracture patterns to better elucidate if unstable intertrochanteric fractures are amenable to treatment with short intramedullary nails. METHODS: This study utilized composite model femurs which were assigned to either a comminuted or reverse obliquity fracture pattern, then subsequently assigned to implantation with either a long or short intramedullary nail. All the samples were reamed to the level of the distal femur and instrumented with the appropriate nail. Axial and torsional stiffness as well as axial load to failure values were determined using a servohydraulic loading system. RESULTS: Short nail constructs exhibited significantly greater axial stiffness in A1 fractures and torsional stiffness in A3 fractures when compared with long nails. There was no significant difference between axial load to failure between long nails and short nails. DISCUSSION: We found no significant difference in axial load to failure values between long and short intramedullary nail fixation in 2 unstable intertrochanteric fracture patterns in a composite femur model. Short nails exhibited greater stiffness in axial loads in the A1 pattern and torsional stiffness in the A3 pattern. This suggests short or long intramedullary nails could be appropriately employed for fixation of unstable intertrochanteric hip fracture patterns.